2007
DOI: 10.4310/hha.2007.v9.n1.a16
|View full text |Cite
|
Sign up to set email alerts
|

$t$-model structures

Abstract: For every stable model category M with a certain extra structure, we produce an associated model structure on the pro-category pro-M and a spectral sequence, analogous to the Atiyah-Hirzebruch spectral sequence, with reasonably good convergence properties for computing in the homotopy category of pro-M. Our motivating example is the category of pro-spectra.The extra structure referred to above is a t-model structure. This is a rigidification of the usual notion of a t-structure on a triangulated category. A t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…Let be a category. As shown in [Fau06] any projectively cofibrant complex in is a retract of a complex that is the filtered colimit of bounded above complexes, each constituted by presheaves that are direct sums of representable ones.…”
Section: Categories Of Adic Motivesmentioning
confidence: 99%
“…Let be a category. As shown in [Fau06] any projectively cofibrant complex in is a retract of a complex that is the filtered colimit of bounded above complexes, each constituted by presheaves that are direct sums of representable ones.…”
Section: Categories Of Adic Motivesmentioning
confidence: 99%
“…t -model categories are discussed in detail in [21]. They give rise to interesting model structures on pro-categories.…”
Section: Definition 84mentioning
confidence: 99%
“…The weak equivalences can be described in terms of pro-homotopy groups, but the reformulation is not quite as obvious as one might expect. See [9,17] for details.…”
Section: Note That R(cp) Equals C(rp)mentioning
confidence: 99%
“…A t-model category is a proper simplicial stable model category C with a tstructure on its (triangulated) homotopy category, together with a lift of the tstructure to C. This notion is studied in detail in [9], where it is shown that a particularly well-behaved filtered model structure on C (and thus a model structure on pro-C) can be associated to any t-model structure on C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation